Design and Application of Smart Distribution Station Area Based on Intelligent Fusion Terminal with Cloud-Edge Coordination - Weiming CHEN; Jinyu CHEN; Yuanliang FAN; Han WU; Zewen LI; Guangda WANG; Yiran LI (Zhongguo dianli)
Intelligent fusion terminal is the core management unit and edge computing tie of smart distribution station area in power distribution Internet of Things (IoT). In order to enhance the practical application of the intelligent fusion terminal in smart distribution station areas, a design method for practical application of smart distribution station area is proposed based on the cloud-edge coordination of the intelligent fusion terminal. Three application cases of low-voltage topology automatic generation, power transmission topology verification, and available capacity analysis are introduced in theory and practice, and the design and its application of the three cases in three levels, including intelligent fusion terminals, distribution station master areas, and mobile devices are elaborated to enhance the intelligence and practicality of distribution station areas. The design and its application can provide a reference for the practical application of the intelligent fusion terminals in distribution IoT with cloud-edge coordination.